Nos natura non sustinet : à propos de l’intensification agricole dans quatre terroirs du nord des Gaules - Pierre Ouzoulias (Gallia)
This article is a critical reappraisal of recent syntheses on ancient demography and it aims at presenting some alternative reflexions. First, the neo-Malthusian historiographic outline, according which the demographic growth of ancient societies would have been blocked by the archaic and non-evolving character of the agriculture and by the law of diminishing returns, is presented. These societies, because they were hampered by the low equilibrium trap, would have remained at a steady state determined by their technological level and by their carrying capacity. According to this economic model, the production capacity of the land is often considered as an exogenous factor and is thought to be determined mainly by its natural characteristics.To this outline are opposed the ideas of Esther Boserup, who considers that the demographic pressure may be the cause of the agricultural intensification and of the exploitation of new land. This paradigm is used to analyze the expansion of agriculture in four areas of northern Gaul. In these four cases, family farms are responsible for the expansion, by means of adjustments of the ager and improvements of the soil agricultural capability. In conclusion is offered a reflexion on the social and economic circumstances of these processes and on the capacity of the Gallo-Roman societies to “make agricultural lands”.